2022
DOI: 10.3389/fbioe.2022.866419
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Inhibition of Agricultural Soil Pathogen Stimulated by Nitrogen-Reducing Fertilization

Abstract: Plant health is the fundamental of agricultural production, which is threatened by plant pathogens severely. The previous studies exhibited the effects of different pathogen control strategies (physical, chemical, and microbial methods), which resulted from bringing in exogenous additives, on microbial community structures and functions. Nevertheless, few studies focused on the potential inhibitory abilities of native microbial community in the soil, which could be activated or enhanced by different fertilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Environmental factor correlation analysis at the genus level showed that Tausonia and Solicocozyma under the Basidiomycota phylum were significantly positively correlated with continuous cropping years, consistent with previous studies on continuous cropping of sugar beet (Cui et al, 2022). Previous studies have shown that under the reduced nitrogen fertilizer environment of tobacco, the abundance of Tausonia significantly increased (Shen et al, 2022). Tausonia may participate in regulating tobacco sugar content and may also play a role in plant tolerance to low temperature and fermentation processes (Kim et al, 2020;Wang et al, 2022b).…”
Section: Discussionsupporting
confidence: 88%
“…Environmental factor correlation analysis at the genus level showed that Tausonia and Solicocozyma under the Basidiomycota phylum were significantly positively correlated with continuous cropping years, consistent with previous studies on continuous cropping of sugar beet (Cui et al, 2022). Previous studies have shown that under the reduced nitrogen fertilizer environment of tobacco, the abundance of Tausonia significantly increased (Shen et al, 2022). Tausonia may participate in regulating tobacco sugar content and may also play a role in plant tolerance to low temperature and fermentation processes (Kim et al, 2020;Wang et al, 2022b).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies focused on using microbial antagonists for controlling soil-borne diseases, and many biocontrol agents were found virtually for plant disease biocontrol against a single pathogen ( Dunne et al., 1997 ; Liu et al., 2007 ; Shanks et al., 2012 ; Han et al., 2016 ). However, managing just one of the pathogens may not fully solve the problem since different pathogens often co-occur on the same plant, resulting in a disease complex causing synergistic yield losses ( Shen et al., 2022 ). An environmentally friendly alternative could be using multiple strains with a broad spectrum of antagonism against multiple pathogens, which may provide excellent and new options for soil-borne disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Good soil conditions are needed for high-quality tobacco production ( Mallikharjuna Rao et al, 2016 ; Begum et al, 2021 ; Shen et al, 2022 ). To achieve sustainable tobacco production, soil quality must be improved ( Wang et al, 2019 ; Yan et al, 2019 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%